Asmalibrasi by Soegi Bornean: A Study of Song Form and Meaning - Alya Nada Satyawidya (Repertoar, 2026)
This study aims to examine the structure and musical meaning in Soegi Bornean's song Asmalibrasi using a musical form analysis and musical aesthetics approach. As a popular musical work rich in expression, Asmalibrasi is worth further analysis, not only in its lyrics but also in its musical elements as written in the score. The method used is a qualitative descriptive approach with score analysis, including observation of song form, expression marks, dynamics, articulation, and harmonic progression. The results of the study show that this song has a three-part form (A–B–A′) with divisions into intro, verse, chorus, bridge, interlude, and coda. Expression marks play an important role in shaping emotional meaning. Changes in dynamics, chord progressions, and phrase structure show an emotional journey from calm to climax and back to silence. In conclusion, Asmalibrasi is not only pleasant to listen to but also features a strong, expressive musical structure. This song shows that popular music can be analyzed scientifically and contains deep aesthetic value.